ANALISIS KEBIJAKAN PANGKALAN UTAMA TNI AL DALAM MENGAMANKAN PANGKALAN ARMADA RI - Risahdi Risahdi (Institut Pemerintahan Dalam Negeri, 2017)
This research is based on the low of security performance of the bases from the sea aspect of the warship ship RI that was leaning. Improving the performance of the security system of the base, especially from the sea aspect is not only required to secure the strategic system of TNI AL but to show the international world that the security system of the Navy base of Indonesia already has World Class Navy qualities so it is expected to invite the presence of other countries warships to lean and enjoy such security guarantees. The presence of warships of various countries will be a parimeter of the territorial of Indonesia in the eyes of the world that will increase the maritime activities of the world in the territory of Indonesia. The purpose of this study is to analyze and describe the existing conditions of the Primary Base Policy in securing the Base Armada RI from the sea aspect to further explain the factors that can influence the policy.